A monitoring of allantoin, uric acid, and malondialdehyde levels in plasma and erythrocytes after ten minutes of running activity - Kanďár, R; Štramová, X; Drábková, P; Křenková, J (Physiological research, 2014)
Uric acid is the final product of human purine metabolism. It was pointed out that this compound acts as an antioxidant and is able to react with reactive oxygen species forming allantoin. Therefore, the measurement of allantoin levels may be used for the determination of oxidative stress in humans. The aim of the study was to clarify the antioxidant effect of uric acid during intense exercise. Whole blood samples were obtained from a group of healthy subjects. Allantoin, uric acid, and malondialdehyde levels in plasma and erythrocytes were measured using a HPLC with UV/Vis detection. Statistical significant differences in allantoin and uric acid levels during short-term intense exercise were found. Immediately after intense exercise, the plasma allantoin levels increased on the average of 200 % in comparison to baseline. Plasma uric acid levels increased slowly, at an average of 20 %. On the other hand, there were no significant changes in plasma malondialdehyde. The results suggest that uric acid, important antioxidant, is probably oxidized by reactive oxygen species to allantoin. Therefore allantoin may be suitable candidate for a marker of acute oxidative stress.
Keywords: Young Adult; Hemoglobins; Lactic Acid; Male; kyselina močová; biologické markery; Allantoin; Biomarkers; mladý dospělý; reaktivní formy kyslíku; alantoin; Adult; dospělí; mužské pohlaví; hemoglobiny; Uric Acid; Malondialdehyde; zátěžový test; Reactive Oxygen Species; běh; Exercise Test; kyselina mléčná; lidé; ženské pohlaví; Humans; malondialdehyd; erytrocyty; Erythrocytes; Running; Female